중증 다발성 늑골골절에 대한 조기 수술적 늑골고정술 - 황정주; 김영진; 류한영; 조현민 (Daehan oe'sang haghoeji, 2011)
Purpose: A rib fracture secondary to blunt thoracic trauma continues to be an important injury with significant complications. Unfortunately, there are no definite treatment guidelines for severe multiple rib fractures. The purpose of this study was to evaluate the result of early operative stabilization and to find the risk factors of surgical fixation in patients with bilateral multiple rib fractures or flail segments. Methods: From December 2005 to December 2008, the medical records of all patients who underwent operative stabilization of ribs for severe multiple rib fractures were reviewed. We investigated patients’ demographics,preoperative comorbidities, underlying lung disease, chest trauma, other associated injuries, number of surgical rib fixation, combined operations, perioperative ventilator support, and postoperative complications to find the factors affecting the mortality after surgical treatment. Results: The mean age of the 96 patients who underwent surgical stabilization for bilateral multiple rib fractures or flail segments was 56.7 years (range: 22 to 82 years), and the male-to-female ratio was 3.6:1. Among the 96 patients, 16 patients (16.7%) underwent reoperation under general or epidural anesthesia due to remaining fracture with severe displacement. The surgical mortality of severe multiple rib fractures was 8.3% (8/96),7 of those 8 patients (87.5%) dying from acute respiratory distress syndrome or sepsis. And the other one patient expired from acute myocardial infarction. The risk factors affecting mortality were liver cirrhosis,chronic obstructive pulmonary disease, concomitant severe head or abdominal injuries, perioperative ventilator care, postoperative bleeding or pneumonia, and tracheostomy. However, age, number of fractured ribs, lung parenchymal injury, pulmonary contusion and combined operations were not significantly related to mortality. Conclusion: In the present study, surgical fixation of ribs could be carried out as a first-line therapeutic option for bilateral rib fractures or flail segments without significant complications if the risk factors associated with mortality were carefully considered. Furthermore, with a view of restoring pulmonary function, as well as chest wall configuration, early operative stabilization of the ribs is more helpful than conventional treatment for patients with severe multiple rib fractures. (J Korean Soc Traumatol 2011;24:12-17) KCI Citation Count: 3